2022
DOI: 10.3389/fonc.2021.814544
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab Plus Chemotherapy in Metastatic Thymic Carcinoma: A Case Report

Abstract: Metastatic thymic carcinomas have a poor prognosis. Pembrolizumab, an anti-PD-1 antibody, has recently been evaluated for patients with metastatic thymic carcinomas progressing after at least one line of platinum-based chemotherapy. The antitumor activity of immunotherapy appears to be promising for these patients and pembrolizumab in monotherapy is actually a treatment option in second metastatic line. To the best of our knowledge, we report the first case of a patient treated for metastatic thymic adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Other studies could look more broadly at the contribution of telemedicine for thoracic oncology pathologies, such as mesothelioma or thymic tumors, for which therapeutic progress is constant. 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies could look more broadly at the contribution of telemedicine for thoracic oncology pathologies, such as mesothelioma or thymic tumors, for which therapeutic progress is constant. 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al reported a progression-free survival of 7.9 months in patients with thymic carcinoma with a low PD-L1 expression treated with a combination of platinum-based chemotherapy (carboplatin plus pemetrexed) and pembrolizumab as a third-line therapy followed by maintenance therapy with pembrolizumab plus pemetrexed [ 18 ]. Thomas et al believe that a chemoimmunotherapy combination is an effective therapeutic approach for thymic carcinoma with low PD-L1 expression [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al reported a progression-free survival of 7.9 months in patients with thymic carcinoma with a low PD-L1 expression treated with a combination of platinumbased chemotherapy (carboplatin plus pemetrexed) and pembrolizumab as a third-line therapy followed by maintenance therapy with pembrolizumab plus pemetrexed [18]. Thomas et al believe that a chemoimmunotherapy combination is an effective therapeutic approach for thymic carcinoma with low PD-L1 expression [18]. In the current case, whether the tumor was thymic carcinoma or lung cancer was difficult to distinguish because the histological type of the tumor was squamous cell carcinoma, and the tumor was CT-guided biopsy of a pleural region showing high accumulation by PET-CT scan was performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations